Cassava Waste Starch as a Source of Bioplastics: Development of a Polymeric Film with Antimicrobial Properties - Yuri D. O. Silveira; Adriana S. Franca; Leandro S. Oliveira (Foods)
Polysaccharides represent the most abundant biopolymers in agri-food wastes and thus are the most studied polymers to produce biodegradable films for use in packaging. Starch is among the major polysaccharides extracted from food and agricultural waste that have been used as precursor material for film production. Therefore, the present study aimed at producing an active film with antimicrobial properties using starch extracted from cassava waste and oil extracted from cloves. The antimicrobial activity of the produced films was tested against Staphylococcus aureus, Salmonella Typhimurium and Listeria monocytogenes. Cassava periderm and cortex were bleached with either NaClO or H2O2 before starch aqueous extraction. The active films’ antimicrobial effectiveness was assessed by the formation of inhibitory halos around film disc samples in an agar diffusion method. The inhibition zone diameters were statistically similar for all microorganisms, with an average diameter of 11.87 ± 1.62 mm. The films presented an average water vapor permeability of 0.14 g mm/m2 h kPa, an average tensile strength of 0.17 MPa and an elongation at break of 32.90%. Based on the determined properties, the produced films were deemed adequate for use in food packaging, in which antimicrobial activity is paramount.